Impact of Project Complexities on Cost Overruns - Gopika Nair*; Sushil Kumar Solanki (International Journal of Architectural Design and Planning, 2023)
As decision-making and goal setting become more challenging due to complexity, there is growing consensus that comprehending complexity is essential for project management. However, there have been concerns expressed regarding how complexity can be quantified in a reliable way that takes into account structural, dynamic, and interaction factors. Current operational definitions of complex projects based on size and budget, have been called into doubt. What can be done is to rank complexities based on their impact and focus on the most impactful complexity dimensions to keep a check on cost overruns leading from them. This study addresses the challenging issues of defining complexity and a complex construction project from the literature and the field. To continue the analysis of the phenomena mentioned in this initial study, a research agenda is suggested. The project complexity uncertainties that could have positive or negative effects on the project's cost and timeline performance can be reduced as a consequence of this investigation. The comprehensive checklist developed for complexity dimensions will serve as a checklist for project managers for identifying which of these dimensions and how many of them are present at each stage of a construction project; and the mitigation strategies that can be adopted at each stage to have a tight grip on project cost.
Keywords: Complexity science; Cost Overrun; construction engineering; project management